The complete mitochondrial genome of a stonefly species, Indonemoura auriformis (Plecoptera: Nemouridae). Issue 2 (3rd July 2019) - Chen, Mengdan; Wang, Ying; Chen, Jiajia; Cao, Jinjun
Abstract: One new mitochondrial genome of Indonemoura auriformis from the family Nemouridae (Insecta: Plecoptera) was sequenced in the study. The mitochondrial genome has the length of 15, 718 bp, encoding 37 genes: 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, and 2 ribosomal RNA (rRNA) genes. The whole nucleotide composition biased adenine and thymine with A + T accounting for 69.9%. Nine PCGs and 14 tRNA genes are encoded in the J chain, the other four PCGs, eight tRNAs, and two rRNA genes are encoded in the chain of N. The mitochondrial genome includes 13 gene overlaps and 12 intergenic spacers. Most PCGs strictly use the ATN as start codon, and terminate with traditional stop codon (TAA and TAG). Except the tRNA Ser(AGN) seems to lack dihydrogen glycine arm, all tRNA genes of the mitochondrial genome are the typical clover secondary structure. The phylogenetic tree of PCGs dataset based on bayesian inference (BI) and maximum likelihood (ML) analysis show the same tree topology. Both ML and BI analysis support the sister-group relationship between Amphinemuria and Nemoura . Meanwhile, Capniidae is closely related to Taeniopterygidae.